Correction: DMT1 iron uptake in the PNS: bridging the gap between injury and regeneration. Issue 12 (6th November 2015) - Martinez-Vivot, Rocío; Copello, Guillermo; Leal, Maria Celeste; Piñero, Gonzalo; Usach, Vanina; Rozenszajn, Mijael; Morelli, Laura; Setton-Avruj, Clara Patricia
Abstract : Correction for 'DMT1 iron uptake in the PNS: bridging the gap between injury and regeneration' by Rocío Martinez-Vivot et al., Metallomics, 2015, 7, 1381–1389.